Distribusi frekuensi lebar anteroposterior sinus frontalis dengan radiograf lateral cephalometri berdasarkan usia dan jenis kelamin - Ilona Karista Julianton; Muhammad Novo Perwira Lubis (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: This research is aimed to determine the wide frequency distribution of anteroposterior frontal sinus with lateral cephalometric radiographs based on age and sex in West Jakarta, which is centered on RSGM FKG Trisakti University. Material and Methods: This research is using descriptive observational research design and the anteroposterior width measurement of the frontal sinus uses the Erturk measurement method. This study used 125 lateral cephalometric radiographs (40 males and 85 females) as samples which taken from a server at the Dental Radiology Installation, RSGM FKG Trisakti University. Results: The result showed that the smallest mean width of the anteroposterior frontal sinuses in males is at 7 years (5.4 mm) and the largest size is at 19 years (9.76 mm). Whereas the smallest mean width of anteroposterior frontal sinuses in females is at the age of 7 years (5.4 mm) and the largest size is at the age of 20 years (9.25 mm). The average width of anteroposterior frontal sinuses is 6.6 mm in males and 5.58 mm in females. Conclusion: Males have an average width of anteroposterior frontal sinuses that is larger than females and there are some decrease in size in some age groups. Variations in size can occur due to genetic and environmental factors.